Relationship of Emergency Ambulance Response Time to Australasian Triage Scale (ATS) Level in Non-Trauma Case Patients - Arianto, Okdwi Ganda; Astuti, Zulmah; Dirdjo, Maridi M (Jurnal Kesehatan, 2024)
Emergency ambulance is an emergency service carried out outside the hospital, both trauma and non-trauma, which is carried out to prevent death and further disability. This service is carried out by increasing the ambulance response time. Emergency ambulance response time in pre-hospital emergency services can impact the assessment of patient triage levels in the development of modern triage, one of which is the Australasian Triage Scale (ATS). This study aims to determine the relationship between emergency ambulance response time and the Australasian Triage Scale (ATS) triage level in non-trauma case patients in Samarinda. The design of this study used a quantitative method, namely descriptive correlation, using a cross-sectional research design. The population in this study was 78 patients. Sampling used the total sampling technique. The instruments used in this study were observation sheets, stopwatches (response time), and the Australasian Triage Scale (ATS). This study was conducted for 3 months from March to May in Public Hospital Samarinda in 2024. Meanwhile, the person correlation test results found a p-value of 0.000<0.05, which means there is a relationship between the emergency ambulance response time to ATS Triage and an r-value of 0.767 where the strength of the relationship is high/strong. With a positive correlation result, the direction of the relationship is in the same direction. This means that the faster the emergency ambulance response time, the better (lower) the emergency condition of non-trauma patients based on the ATS triage level.